TRANSFORMING ARABIYA BAINA YADAIK LEARNING: GROUP AND INDIVIDUAL REMEDIAL STRATEGIES FOR ACADEMIC ACHIEVEMENT - Arifdo Putra; Mahyudin Ritonga; Rahmawati Rahmawati (Universitas Islam Negeri Mataram, 2024)
The Arabic language learning using the book